The Extent of Availability of Mathematical Communication Skills in the Developed Mathematics Textbook for Seventh Grade in Jordan - Abu Fares, Shahed Ahmed; Al-Shannaq, Ma’moon Mohammad (Dirasat: Educational Sciences, 2023)
Objectives: This study aimed to identify the availability of mathematical communication skills in the content of the mathematics textbook for the seventh grade in its first and second semesters in Jordan. Methods: To achieve the objectives of the study, a descriptive approach content analysis was adopted. The instrument of content analysis was prepared, including (38) items distributed into four mathematical communication skills: mathematical reading skill, mathematical writing skill, mathematical discussion skill, and mathematical representation skill. The validity and reliability of the instrument were verified. The study population and its sample were represented by the content of a mathematics textbook for the seventh grade in Jordan. Results: The results indicated that the mathematical reading skill ranked first with a high availability rate reached (37.43%), followed by the mathematical writing skill in the second order with a high availability rate of (34.07%). The third rank was the mathematical representation skill with a low availability (14.35%), and the mathematical discussion skill was in the final rank with a low availability rate of (14.15%). The results also showed the different interest of items and their rate frequency and ignorance of some items that did not get any opportunity. Conclusions: The study recommended giving essential attention to the mathematical communication skills in a better way in mathematics textbooks and conducting more studies related to content analysis.